2015
DOI: 10.1523/eneuro.0044-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of Target Dependence by Developing Rat Retinal Ganglion Cells

Abstract: Similar to neurons in the peripheral nervous system, immature CNS-derived RGCs become dependent on target-derived neurotrophic support as their axons reach termination sites in the brain. To study the factors that influence this developmental transition we took advantage of the fact that rat RGCs are born, and target innervation occurs, over a protracted period of time. Early-born RGCs have axons in the SC by birth (P0), whereas axons from late-born RGCs do not innervate the SC until P4-P5. Birth dating RGCs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 171 publications
6
23
2
Order By: Relevance
“…In the rat it has been shown that axons from early‐born (E13–E15) RGCs are present in the SC at birth (Bunt et al, ; Dallimore et al, ), whereas axons of later‐born (E18–E19) RGCs do not grow into the SC until approximately P4–P5 (Dallimore et al, ). Importantly, RGCs born on different days die at different times, the timing of death in a particular age cohort related to when their axons reach central targets (Dallimore et al, ; Moses et al, ). We analyzed a snapshot of RGC death on specific postnatal days, at a time when, depending on their birthdate, RGC axons have either just grown into the SC or had entered some time before birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rat it has been shown that axons from early‐born (E13–E15) RGCs are present in the SC at birth (Bunt et al, ; Dallimore et al, ), whereas axons of later‐born (E18–E19) RGCs do not grow into the SC until approximately P4–P5 (Dallimore et al, ). Importantly, RGCs born on different days die at different times, the timing of death in a particular age cohort related to when their axons reach central targets (Dallimore et al, ; Moses et al, ). We analyzed a snapshot of RGC death on specific postnatal days, at a time when, depending on their birthdate, RGC axons have either just grown into the SC or had entered some time before birth.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely alternative is that most RGC death occurs stochastically, and is due to some form of competition for neurotrophic factors (Oppenheim, 1991). Developing RGCs with axons not yet in central targets such as the SC depend on local neurotrophic support for their survival (Spalding et al, 2004;Moses et al, 2015). However, upon innervation, there is a switch towards target derived neurotrophic dependence, where the parent RGCs begin to rely upon neurotrophins secreted by the SC for their continued survival (Ma et al, 1998;Frost et al, 2001;Pollock et al, 2003;Spalding et al, 2004).…”
Section: Interaction Of Independent Developmental Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing neurons rely on neurotrophic support for their survival and maturation (Huang and Reichardt, 2001). Perhaps the most well studied neurotrophin in RGC development is BDNF, whose neuroprotective effects on RGCs have been documented in vivo and in vitro (Johnson et al, 1986;Ma et al, 1998;Spalding et al, 2004;Moses et al, 2015). BDNF is synthesized and can be released as pro-BDNF to act on the p75 receptor, or the pro domain can be cleaved to produce mature BDNF that acts on the high affinity tropomyosin receptor kinase B (TrkB) receptor to bring about neuroprotective effects (Nagappan and Lu, 2005;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is synthesized and can be released as pro-BDNF to act on the p75 receptor, or the pro domain can be cleaved to produce mature BDNF that acts on the high affinity tropomyosin receptor kinase B (TrkB) receptor to bring about neuroprotective effects (Nagappan and Lu, 2005;Yang et al, 2009). BDNF and TrkB mRNA and proteins are detected in early embryonic development in RGCs, the levels of expression changing throughout development (Ernfors et al, 1992;Jelsma et al, 1993;Koide et al, 1995;Perez and Caminos, 1995;Vecino et al, 2002;Moses et al, 2015). However, neurotrophins are also produced in the SC and can be retrogradely transported to the retina via RGC axons (Ma et al, 1998;Frost et al, 2001;Spalding et al, 2002Spalding et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%